2017
DOI: 10.1039/c7fo01273j
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxant activity of twenty-one physiologically relevant (poly)phenolic metabolites on isolated mouse arteries

Abstract: Polyphenols are beneficial for health, but are metabolised after consumption. We compared the vasorelaxant capacity of twenty-one physiologically relevant polyphenol metabolites in isolated mouse arteries. Hesperetin, urolithins and ferulic acid-4-O-sulfate - not their glucuronidated forms or ferulic acid - caused vasorelaxation. Therefore, we advise the use of relevant conjugates in future mechanistic research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…This lack of anti‐inflammatory activity was consistent with previous data observed for other activities of Uro such as antiproliferative, vasorelaxant, and (or) estrogenic, suggesting that phase‐II conjugation of Uro dampens their biological activity in vivo and in vitro. [ 47–49 ] Although free Uro are hardly detected in the bloodstream, a recent in vivo study has shown deconjugation of Uro‐A glucuronide to Uro‐A in a systemic LPS‐induced inflammation rat model, suggesting presence of free Uro‐A in microenvironments subjected to inflammatory stimuli. [ 50 ] Nevertheless, the capacity of leukocytes to hydrolyze Uro has not been investigated, justifying future studies on the metabolism of Uro by human leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of anti‐inflammatory activity was consistent with previous data observed for other activities of Uro such as antiproliferative, vasorelaxant, and (or) estrogenic, suggesting that phase‐II conjugation of Uro dampens their biological activity in vivo and in vitro. [ 47–49 ] Although free Uro are hardly detected in the bloodstream, a recent in vivo study has shown deconjugation of Uro‐A glucuronide to Uro‐A in a systemic LPS‐induced inflammation rat model, suggesting presence of free Uro‐A in microenvironments subjected to inflammatory stimuli. [ 50 ] Nevertheless, the capacity of leukocytes to hydrolyze Uro has not been investigated, justifying future studies on the metabolism of Uro by human leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This could be relevant in human subjects belonging to the UM‐A metabotype (80% Uro‐A and 20% Uro‐C), and UM‐B (50% IsoUro‐A, 20% Uro‐B, 20% Uro‐A, 10% Uro‐C) compared to UM‐0 (non‐producers of Uro). [ 18,48,49 ] To determine whether these metabotypes are relevant in IBD, carefully designed in vitro and in vivo studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenolic metabolites 3′,4′,5′-trihydroxyphenyl)-γ-valerolactone and 5-(3′,5′-dihydroxyphenyl)-γ-valerolactone also displayed, in spontaneously hypertensive rats, the capacity to lower angiotensin-1 converting enzyme activity and blood pressure, both contributing to improving endothelial function and arterial elasticity [ 235 ]. Paradoxically, the flavan-3-ol metabolites 5-(3′,4′,5′-trihydroxyphenyl)-γ-valerolactone, 5-(3′,4′-dihydroxyphenyl)-γ-valerolactone, and 5-(3′-methoxy, 4′-hydroxyphenyl)-γ-valerolactone did not improve vascular endothelial plasticity of freshly isolated mouse saphenous arteries [ 236 ]. The dissimilarity in data could partially be explained by the different models used, especially that isolated saphenous artery endothelium is less reactive than the vessels of the spontaneously hypertensive rat.…”
Section: Polyphenol Metabolitesmentioning
confidence: 99%
“…The tested compounds were purchased from Sigma Aldrich, syringic acid was purchased from Alfa Aesar, and phloroglucinol was purchased from Across Organics. PCA conjugates and gallic acid conjugates were synthesized in-house [40]. After treatment, the luciferase activity was measured as a marker of PON1 promoter activity.…”
Section: Treatmentsmentioning
confidence: 99%